Mental health trends of Korean adolescents before, during, and after the Covid-19 pandemic - Kim, Seojung; Chi, SuHyuk; Chae, Boram; Lee, Jongha (Acta psychologica, 2025)
The coronavirus disease-2019 pandemic has severely affected mental health. This study aimed to examine the patterns and differences in mental and behavioral health in adolescents across distinct pandemic phases. Data for a total of 278,989 adolescents from the KYRBS, covering the pre-pandemic (2018–2019), during-pandemic (2020−2021), and post-pandemic (2022) periods, were analyzed. Subgroups were compared based on sex, age, and socioeconomic status. Multiple linear regression analyses were conducted to examine temporal changes in perceived stress, sleep recovery, and physical activity during the pandemic period. The proportion of adolescents who reported feelings of perceived stress within the last 12 months exhibited a slight decline at the onset of the COVID-19 pandemic, followed by a rebound, and subsequently showed a marked increase in the post-pandemic period. Female and high-school students consistently exhibited high-stress levels across all time points, and adolescents from low socioeconomic backgrounds reported persistently high stress with minimal fluctuation. The findings highlighted the unequal impact of the pandemic on different adolescent populations, suggesting the need for targeted mental health support and recovery strategies. This study underscores the importance of understanding subgroup variations in order to effectively address the long-term effects of global crises on the mental health of adolescents. •Perceived stress decreased during COVID-19, then rose significantly post-pandemic.•Female and high school students consistently reported higher stress across all phases.•Adolescents from low-SES backgrounds reported persistently high stress with little change.•Our findings highlight the need for targeted interventions aimed at adolescents at heightened risk for mental health issues.